Pengaruh Bullying verbal terhadap tingkat kepercayaan diri korban dan penanganannya dalam Psikologi Konseling - Setiorini, Faradina (Maliki Interdisciplinary Journal, 2024)
It is important to know the effect of verbal bullying on the victim’s level of confidence and its handling so that people know more about how verbal bullying behavior is, so that they are able to defend themselves if they feel they are experiencing verbal bullying. This is because verbal bullying behavior is hidden behavior, not physical and will have a negative impact on a person’s psychological condition. This article aims to educate the public about the devastating effects of verbal bullying on both victims and perpetrators. Thus, people can be more aware of the environment and people around them. In counseling science, one of the treatments that can be given to victims of bullying is by using coping strategies. Coping strategy is a process where someone tries to manage the stress they experience in a certain way, so that they can get out of a stressful situation and as a form of self-defense.